Leakage current analysis on polymeric and non-polymeric insulating materials using time-frequency distribution - Abdullah, Abdul Rahim; NORDDIN, NURBAHIRAH; Zainal Abidin, Nur Qamarina; Aman, Aminudin; JOPRI, MOHD HATTA (2012)
This paper presents the performance of polymeric and non-polymeric insulation material in contaminated condition. The purpose of this study is to determine the accuracy of analysis technique on the performance these types of insulation against its tracking and erosion. Polypropylene and glass are selected as polymeric and non-polymeric material. Tracking and erosion test complying with BS EN 60587-2007 are conducted, then leakage current frequency components is used as a diagnostic tool for their surface condition monitoring and degradation severity. The analyses of leakage current are based on frequency domain and time-frequency representations are conducted. From the results, the surface condition of polymeric insulation material state can be classified accurately by using spectrogram compared to Fast Fourier Transform. It also proved that the performance of tracking and erosion of glass is better than polypropylene material.